If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 35 = 71 Reorder the terms: 35 + 4x = 71 Solving 35 + 4x = 71 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + 4x = 71 + -35 Combine like terms: 35 + -35 = 0 0 + 4x = 71 + -35 4x = 71 + -35 Combine like terms: 71 + -35 = 36 4x = 36 Divide each side by '4'. x = 9 Simplifying x = 9
| 5q+6=10q-3 | | a-3t=5t^2 | | x^2-12x+1=o | | 29-2x+7=-3x-11 | | 2x^2-y+3=x | | t/5-3=15 | | (2x-1)(x+5)=O | | 2m+5=33 | | v-1/5=-1/5v-5/2 | | 2ln(x)=ln(3x+10) | | x/3-x/4 | | 40a+30b=630 | | X^2+y^2-4x+6y+2k-1=0 | | G/12-13=14 | | 3+4x+20-30=90 | | X^2-3x-8=7x-29 | | x-2=x+12 | | 3.2-7y=16y-1.89 | | 3x+20x+60-x-3= | | 3x-20x+60-x+3= | | -18x+63= | | 2744)1/3 | | 3x+5(-4x+12)-(x-3)= | | 9x^2+12+4=6 | | 7(2x-1)+5y-6=3y-2(3y)+3 | | 2/3x9/8 | | (4x)m+(5x+1)+(5x+3)m=102 | | -3b-5b-2b=80 | | -12r+15r=21 | | 10z+2z-13z=45 | | 18a-14a=36 | | -3s+8s-10s=35 |